Pre-treatment lesional volume in older stroke patients treated with endovascular treatment. Issue 10 (December 2022) - Duloquin, Gauthier; Ferrigno, Marc; Hassen, Wagih Ben; Kyheng, Maéva; Bricout, Nicolas; Boulouis, Grégoire; Seners, Pierre; Labreuche, Julien; Turc, Guillaume; Naggara, Olivier; Cordonnier, Charlotte; Henon, Hilde; et al.
Background: Recent studies in the general stroke population treated with endovascular treatment (EVT) reported that higher pre-treatment lesional volumes were independently associated with poor neurological outcome and functional dependence after stroke. However, it has been not evaluated in older patients. Aim: We test the association between the pre-treatment lesional volume on diffusion-weighted magnetic resonance imaging and relevant outcome measures in older adults with stroke treated with EVT. Methods: We included consecutive older adults with stroke (⩾80 years old) treated with EVT in two academic comprehensive stroke centers. The association between pre-treatment lesional volume and relevant outcome measures (poor outcome (modified Rankin scale 4–6), 3-month mortality and symptomatic intracerebral hemorrhage (sICH)) was evaluated using univariate and multivariable models. Results: Five hundred seventy-nine patients were included (mean age: 85.6 ± 4.1, median lesional volume was 10 ml; interquartile range: 3–30 ml). Pre-treatment lesional volume was associated with poor functional outcome (adjusted odds ratio (aOR): 1.87, 95% confidence interval (CI): 1.60–2.20, for +1 logarithmic increase of lesional volume), 3-month mortality (aOR: 1.50, CI: 1.28–1.76), and sICH (aOR: 1.67, CI: 1.27–2.20). A threshold lesional volume >35 ml predicted 90% of patients with poor functional outcome and a cut-off >51 ml predicted 90% of patients dead at 3 months. Conclusions: Pre-treatment lesional volume might contribute, in association with other relevant clinical features, to the selection of older stroke patients who will benefit from EVT.